SYNTHESIS OF POLYVINYL ALCOHOL-CHITOSAN HYDROGEL AND STUDY OF ITS SWELLING AND ANTIBACTERIAL PROPERTIES - Wikanta, Thamrin; Erizal, Mr; Tjahyono, Mr; Sugiyono, Mr (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2012)
The aim of this research was to synthesize a hydrogel for wound dressing by mixing of polyvinyl alcohol (PVA) and chitosan (CTS) and processed by combination technique of freezing-thawing and irradiation by gamma ray, and to study of its properties. PVA aqueous solution 10% (w/v) was mixed with 2% (w/v) chitosan (CTS) solution and homogenized. The PVA-CTS mixture was processed by freezing-thawing up to 3 cycles, and then irradiated by gamma rays at the doseranged of 20-50 kGyÂ  (dose rate was 10 kGy/hour). Result showed that PVA-CTS hydrogel with the gel fraction of 83%, 87%, 90%, and 83% were obtained at the irradiation dose of 20 kGy, 30 kGy, 40 kGy, and 50 kGy, respectively. Increasing of irradiation dose caused increasing of water absorption of hydrogel, i.e. 1.700 %, 1.715 %, 1.913 %, and 2.036 %, respectively, and the hydrogel reached the equilibrium in 25 hours. The hydrogel showed very slow water evaporation rate (~ 2%) at the initial time (1 hour) and then increased very fast (up ~50 %) at 24 h, i.e. 43%, 39.13%, 44%, and 53%, respectively. The elongation at break of hydrogels were obtained 245%, 322%, 322%, and 205% with the maximum value were obtained at irradiation dose ranged of 30-40 kGy. The presence of chitosan in the PVA hydrogel made it having higher antibacterial properties with the inhibitionzone value of 8 mm at irradiation dose of 30-40 kGy compared to PVA hydrogel as a negative control (6 mm) and to chloramphenicol as a positive control (8 mm).